Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/plants9040490
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Artificial Light for Spinach Growth in Plant Factory Based on Orthogonal Test

Abstract: Artificial LED source provides the possibility to regulate the lighting environment in plant factorys that use limited space to plant, aiming at high throughput and good quality. However, different parameters of light intensity, quality, and photoperiod will influence the growth and accumulation of bio-compounds in plants. In order to find the optimal setting of LED light for spinach planting, four group experiments were designed using the orthogonal testing method. According to the experimental results, for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 29 publications
0
19
0
2
Order By: Relevance
“…The optimization results of this study showed that GA, PSO, and MVO effectively determine the best global solution for nonlinear problems such as the maximization of chlorophylla concentrations as a function of carbon dioxide, light intensity, air temperature, and humidity (Table 2). Prior studies have reported that for soilless lettuce cultivation, the acceptable threshold for carbon dioxide concentration, light intensity, temperature, and humidity is 803.019 to 1300 ppm [17], [21], ≥ 175.23 μmol m -2 s -1 [15], [17], [23], 18 to 23 °C [14], [17], [18], and 60% to 75% [14], respectively. Based on the converged best solutions of GA, the temperature is above the ideal range, and the humidity is slightly short (Table 2).…”
Section: Photosynthetic and Respiration Rates Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization results of this study showed that GA, PSO, and MVO effectively determine the best global solution for nonlinear problems such as the maximization of chlorophylla concentrations as a function of carbon dioxide, light intensity, air temperature, and humidity (Table 2). Prior studies have reported that for soilless lettuce cultivation, the acceptable threshold for carbon dioxide concentration, light intensity, temperature, and humidity is 803.019 to 1300 ppm [17], [21], ≥ 175.23 μmol m -2 s -1 [15], [17], [23], 18 to 23 °C [14], [17], [18], and 60% to 75% [14], respectively. Based on the converged best solutions of GA, the temperature is above the ideal range, and the humidity is slightly short (Table 2).…”
Section: Photosynthetic and Respiration Rates Assaymentioning
confidence: 99%
“…Far-red (FR) light has a positive impact on the photomorphogenesis of greenhouse plants [20], monochromatic red and blue lights result in to decrease in stomatal density [21], and red-blue and yellow spectrums affect the air temperature and humidity [22]. The combination of red-blue light (4:1) and 15 hours photoperiod has been tested effective for spinach [23]. The photoperiod of consecutive 15 light hours and 22 hours for dark-period respiration suggested an increase in photosynthetic rate as expressed by low starch content in the leaf [24].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of greenhouse agriculture, plant factory production and greenhouse light supplementation have become key technologies in protected horticulture production. Hydroponics in plant factories offers numerous advantages, such as high yield, good quality, continuous production, efficient resource utilization, and avoidance of the impacts of environment change; it has been used to solve the unstable vegetable supply and the pollution of land resources (Viršilë et al, 2020;Zou et al, 2020). However, hydroponics production can cause the accumulation of nitrate nitrogen in plants, especially in leaf vegetables, such as lettuce (Lactuca sativa L.) (Rouphael et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of lighting environment is one major challenge to promote availability for plant production in green house or plant factory (Rehman et al, 2017;Zou et al, 2020). Lighting environment, including the light spectrum, intensity, and photoperiod, regulates plant morphogenesis, plant photosynthetic differentiation and growth (Hughes, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, green light has also been reported to contribute to photosynthesis in plants (Smith et al, 2017). For optimization of lighting environment, light-emitting diodes (LEDs) provide light within the required narrow spectrum for plant photosynthesis, morphogenesis, and growth (Rehman et al, 2017), and allows an evaluation of the spectrum composition necessary to provide optimal plant production conditions (Zou et al, 2020). Different spectral light induces distinct morphogenetic and photosynthetic responses that vary depending on plant species and/or cultivars (Chen et al, 2014;Clavijo-Herrera et al, 2018).…”
Section: Introductionmentioning
confidence: 99%